Effect of architectural angularity on refugia selection by the brown spider, Loxosceles gaucho - Stropa, A. A. [UNESP] (Wiley-Blackwell, 2010)
Some brown spider species infest man-made environments and pose a threat to human health. Because habitat architecture affects spider populations, I evaluated the preferences of individuals of Loxosceles gaucho (Gertsch) (Araneae: Sicariidae) for refugia with different angular structures. Four differently angled refugia models (acute-, right-, obtuse-angled and cylindrical) were placed on the litter of a forest fragment and observed each month for 1 year. Females of this species were found to prefer refugia with acute angles. This finding brings new information to our understanding of brown spider infestations in man-made environments: refugia with acute angles are likely to offer more protection for females and their offspring.
Keywords: Loxosceles; anthropic environment; arachnidism; brown recluse spider; habitat selection; loxoscelism; refugia architecture; spider control; urban entomology